Managing the risks of shadow IoT. Issue 1 (January 2019) - Cox, Gary
Abstract : Over the past decade, IT teams have been charged with managing the complexities and security risks inherent in their organisations' bring your own device (BYOD) schemes and unsanctioned shadow IT operations. The burgeoning growth of the Internet of Things (IoT) and the plethora of consumer devices being connected to enterprise networks have only exacerbated the situation further, adding new levels of complexity and risk and giving rise to the phenomenon of shadow IoT.